A Long Time Constant May Endorse Sharp Waves and Spikes Over Sharp Transients in Scalp Electroencephalography: A Comparison of After-Slow Among Different Time Constants Concordant With High-Frequency Activity Analysis - Sultana, Shamima; Hitomi, Takefumi; Daifu Kobayashi, Masako; Shimotake, Akihiro; Matsuhashi, Masao; Takahashi, Ryosuke; Ikeda, Akio (Frontiers in Human Neuroscience, 2021)
Objective: To clarify whether long time constant (TC) is useful for detecting the after-slow activity of epileptiform discharges (EDs): sharp waves and spikes, and for differentiating EDs from sharp transients (Sts). Methods: We employed 68 after-slow activities preceded by 32 EDs (26 sharp waves and six spikes) and 36 Sts from 52 patients with partial and generalized epilepsy (22 men, 30 women; mean age, 39.08 ± 13.13 years) defined by visual inspection. High frequency activity (HFA) associated with apical component of EDs and Sts was also investigated to endorse two groups. After separating nine Sts, that were labeled by visual inspection but did not fulfill the amplitude criteria for after-slow of Sts, 59 activities (32 EDs and 27 Sts) were analyzed about total area of after-slow under three TC (long: 2 s; conventional: 0.3 s; and short: 0.1 s). Results: Compared to Sts, HFA was found significantly more with apical component of EDs (p < 0.05). Total area of after-slow in all 32 EDs under TC 2 s was significantly larger than those under TC 0.3 s and 0.1 s (p < 0.001). Conversely, no significant differences were observed in same parameter of 27 Sts among three different TC. Regarding separated nine Sts, total area of after-slow showed a similar tendency to that of 27 Sts under three different TC. Significance: These results suggest that long TC could be useful for selectively endorsing after-slow of EDs and differentiating EDs from Sts. These findings are concordant with the results of HFA analysis. Visual inspection is also equally good as total area of after-slow analysis.